Strengthening Bumdes Governance as A Village Economic Growth Milletle - Rahman Towadi; Amanda Adelina Harun (Estudiante Law Journal, 2022)
This study aims to analyze the management of BUMDes in strengthening economic enterprises in Teratai Village, Tabongo District, Gorontalo Regency, and to find out the constraints of BUMDes in strengthening economic enterprises in Teratai Village, Tabongo District, Gorontalo Regency. this type of research is a type of empirical juridical research. The approaches used by researchers in compiling this research are, among others: the Legislative Approach (Statue Approach) and the case approach (case approach). In this case, the data collection that will be used in this study includes several steps, namely through observation, interviews, and documentation. The results of the study indicate that the management of BUMDes in strengthening economic business in the Teratai village has been running effectively, as seen from the several business units that have been run which have been able to increase the economy and village income. There are several obstacles faced in the management of BUMDes, namely human resources and inadequate facilities and infrastructure.